New Media and Gender Inequality during Political Campaigns in Kosovo: Array - Rexha, Gjylie (Acta Universitatis Danubius. Communicatio, 2021)
Political parties in Kosovo randomly adhere to legal obligations to quotas for women in parliament. But, during campaigns, female candidates do not appear as leaders in debates and political activities. This paper focuses the campaign for parliamentary election in 2019. We have monitored the stories about campaign in three online media, presented on their Face book pages. The results obtained from the content analyses argue that women are presented only as integral part of the political parties’ lists and electoral activities. Consequently, during political campaigns, they are under presented within the parties and in media coverage.